STROMATOLITES FROM BASHKIRIAN DEPOSITS OF DONETS BASIN - Dernov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is dedicated to the research of unique siliceous stromatolites from limestone G2 (Mospins'ka suite, Upper Bashkirian) of Donets Basin. These biogenic structures exhibit four (lamellar, hemispheroidal, not branching columnar and stratified columnar) morphotypes. In addition, supposedly, small oncolites were identified. According to principles of botanical nomenclature classification, stromatolites must be classified as stiriolites. Stromatolites of primarily siliceous composition form a distinctive group. Stromatolites, as a rule, are indicators of the shallow basin conditions, as the normal development of cyanobacteria is only possible in shallow bodies of water. Numerous lithofacies indicate shallow water formation conditions of limestone G2 . Thus, the examined stromatolites were formed on the upper part of the subtidal zone – with good aeration of waters, at depths up to 20m or less. The extensive development of stromatolites in limestone stands in stark contrast to the almost complete absence of corals in it. This fact indicates an unstable salinity. Part of paleo water area, where siliceous stromatolites are found, had great but local desalination due to the penetration of large amounts of fresh water in the saltwater sea basin. It must have taken place because of significant evaporation. As a result of these processes, concentration of dissolved silica in water sharply increased. Later, when the factor of desalination of water ceased to operate and/or the concentration of silica in the water fell by its binding in the stromatolite structures, cyanobacteria were not able to precipitate SiO2 and stromatolites growth stopped. The origin of the lamellar microstructure of stromatolites is due to seasonal factor: light layers stromatolites were formed under the conditions of sufficiently large amount of precipitation during the rainy season, and the dark ones – in relatively dry seasons. Taking into account large scientific and educational value and uniqueness of examined stromatolites, we think, that some of the outcrops of limestone G2 must acquire status of environmentally protected sites.
Keywords: stromatolites; Carboniferous deposits; Donets Basin